2013
DOI: 10.1021/es303938c
|View full text |Cite
|
Sign up to set email alerts
|

Strategically Placing Green Infrastructure: Cost-Effective Land Conservation in the Floodplain

Abstract: Green infrastructure approaches have attracted increased attention from local governments as a way to lower flood risk and provide an array of other environmental services. The peer-reviewed literature, however, offers few estimates of the economic impacts of such approaches at the watershed scale. We estimate the avoided flood damages and the costs of preventing development of floodplain parcels in the East River Watershed of Wisconsin's Lower Fox River Basin. Results suggest that the costs of preventing conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 25 publications
(44 reference statements)
0
39
0
Order By: Relevance
“…Whipple (1969) argues that zoning should not be applied to all of the floodplain and that rather an optimization routine should be developed to optimally select the areas to be zoned. This is similar to the approach taken in Kousky et al (2013). However, this increases the complexity of the modeling process without necessarily simplifying the determination of the spatial extent of the CBA.…”
Section: Variable Selection For a Cbamentioning
confidence: 85%
See 1 more Smart Citation
“…Whipple (1969) argues that zoning should not be applied to all of the floodplain and that rather an optimization routine should be developed to optimally select the areas to be zoned. This is similar to the approach taken in Kousky et al (2013). However, this increases the complexity of the modeling process without necessarily simplifying the determination of the spatial extent of the CBA.…”
Section: Variable Selection For a Cbamentioning
confidence: 85%
“…This also holds when the exogenous impacts of climate change are taken into account (Aerts et al, ). Kousky et al () also find that targeted land‐use strategies are more likely to offer a net benefit to society. Furthermore, the cases from North America conclude this was mainly due to the avoided flood impacts.…”
Section: Flood Risk Zoning Cbamentioning
confidence: 98%
“…The most common paradigm for assessing the economic benefits of flood risk reduction is quantifying prevented losses. For example, Kousky et al (2013) examined the cost-benefit relationship of preventing conversion of natural and agricultural areas in the floodplain to residential use at the parcel level, and showed that avoided losses mostly offset missed development opportunities. Analyses on the effects of floods commonly estimate and compare losses ex-ante and ex-post, or for current and alternative scenarios (Shreve and Kelman 2014;Poussin et al 2015).…”
Section: Agricultural Practices and Flood Impactsmentioning
confidence: 99%
“…Restoring wetlands, reconnecting incised streams to their floodplains through the removal of retired roads or railroads, and installing structures that mimic the ecological services provided by beavers are all examples of natural infrastructure-based methods of slowing runoff and promoting water retention in dewatered basins [15][16][17][18][19][20][21][22]. Previous research on the feasibility of wetlands and other natural infrastructures to attenuate flood and waste water has yielded promising results [14,[23][24][25][26][27]. Beaver mimicry structures, for instance, can improve water quality and slow water flow, generate riparian vegetation, enhance channel stability and wetland hydrologic processes, deliver ancillary benefits to fisheries, and provide cost-effective natural storage opportunities [15][16][17][18][19]21].…”
Section: Natural Infrastructure and The Quantification Of Natural Watmentioning
confidence: 99%